Equivalência semântica da versão em português do instrumento Abuse Assessment Screen para rastrear a violência contra a mulher grávida Semantic equivalence of the Portuguese version of the Abuse Assessment Screen tool used for the screening of violence against pregnant women - Michael E Reichenheim; Claudia Leite Moraes; Maria Helena Hasselmann (Universidade de São Paulo, 2000)
INTRODUÇÃO: Programas de investigação epidemiológica e de ação no âmbito da violência familiar estão em franca ascensão, requerendo instrumentos de aferição adaptados e vertidos para o português. O objetivo do estudo é avaliar a equivalência semântica entre o original em inglês e duas versões para o português do instrumento Abuse Assessment Screen (AAS) usado no rastreamento de casos de violência contra a mulher grávida e recomendar uma versão-síntese para uso corrente. MÉTODOS: O processo de avaliação de equivalência semântica envolveu quatro etapas: tradução, retradução, apreciação formal de equivalência e crítica final através de consultas com especialista na área temática. RESULTADOS: Para cada item do instrumento apresentam-se os resultados relativos às quatro etapas. O texto cobre cada passo do processo que levou à versão final. As duas versões mostraram-se bastante semelhantes, com 14 das 15 assertivas similares, embora a segunda versão tenha se mostrado mais adequada, ainda que para alguns itens tenha sido decidido juntar as duas versões ou mesmo utilizar um item oriundo da versão um. CONCLUSÃO: É importante usar mais de uma versão no processo, em várias etapas de avaliação e de crítica, e discutir a pertinência de se acrescentar uma etapa adicional de interlocução do instrumento com membros da população-alvo. INTRODUCTION: Research programs and actions regarding family violence have been growing steadily. Therefore, there's a need to develop data collection tools. In Brazil, further problems come up since tools that have been developed elsewhere need to be adapted and translated. This study focuses on the Abuse Assessment Screening (AAS) used to detect violence against pregnant women. The objective is to evaluate the semantic equivalence between the original tool in English and two Portuguese versions, and propose a synthetic version to be used in the field. METHODS: The evaluation of semantic equivalence was carried out in 4 steps: (1) translation, (2) back translation, (3) formal appreciation of equivalence and (4) a final critical assessment by family violence experts. RESULTS: Translation, back translation and the steps 3 and 4 assessment are presented for each item of the tool, along with the original in English. The text covers each discussion that led to the final version. Both versions were quite similar in 14 out of 15 items. Nevertheless, the second version showed to be slightly more adequate although for some items the decision was to combine both versions or, in one case, use an item from version 1. CONCLUSION: The procedure undertaken in this study is discussed in the light of Herdman et al.'s proposal (1998) regarding transcultural equivalence. The study also stresses the importance of using more than one version in the process and the appropriateness of including an additional step about the assessment of the target population's understanding of the tool.